Indicators of quality of educational work at vocational schools - Zakatnov, Dmytro (Professional Pedagogics, 2012)
The article analyzes approaches to determining the effectiveness of educational work at vocational schools. The author shows that certain components of psychological readiness to professional activity which describe an individual from psychological angle can be used as its integral indicators.